A variant of the primitive element theorem for separable extensions of a commutative ring - Bagio, D.; Paques, A. (Algebra and Discrete Mathematics, 2009)
In this article we show that any strongly separable extension of a commutative ring R can be embedded into another one having primitive element whenever every boolean localization of R modulo its Jacobson radical is von Neumann regular and locally uniform.